Hydrological performance of native plant species within extensive green roof system in Malaysia - Fai C.M.; Bakar M.F.B.A.; Roslan M.A.A.B.; Fadzailah F.A.B.; Idrus M.F.Z.B.; Ismail N.F.B.; Sidek L.M.; Basri H. (Asian Research Publishing Network, 2023)
Little is known about the hydrological performances of different native plant species within extensive green roof system in Malaysia. Thus, this research focused on the runoff retention efficiency within extensive green roof system with respect to different native plant species in Malaysia. A total of six green roofs were constructed with five being vegetated and one left unvegetated. Four test beds were vegetated with Nephrolepis bisserata (fern), Axonopus compressus (cow grass), portulaca grandiflora cultivars (sedum) and Zoysia matrella (Manila grass). The fifth test bed was a combination of all species and the six test bed with bare soil acted as control. The runoff volume was measured volumetrically through connected to an surface runoff harvesting tank under the test beds. Water retention was calculated from the difference between the depth of rainfall and the depth of runoff from each test bed. Results showed that mixture of plant species was the most effective vegetation at reducing runoff water. The monoculture of portulaca grandiflora cultivars (sedum) performed the best runoff water retention efficiency for single plant species. 2006-2015 Asian Research Publishing Network (ARPN).